2016
DOI: 10.1007/s00005-016-0395-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of CX3CL1 in Diseases

Abstract: Chemokines are a family of small 8-10 kDa inducible cytokines. Initially characterized as chemotactic factors, they are now considered to affect not just cellular recruitment. CX3CL1 is a unique chemokine that can exist in a soluble form, as a chemotactic cytokine, or in a membrane-attached form that acts as a binding molecule. Recently, the effects of CX3CL1 on diseases, such as inflammation and cancer, have been supported and confirmed by numerous publications. However, due to its dual effects, CX3CL1 exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 127 publications
0
53
0
Order By: Relevance
“…37 In gastric adenocarcinoma, tumor cells secreting CX3CL1 can recruit T cells and NK cells, thus, activating both the adaptive and innate immune responses, leading to prolonged survival. 38 Herein, we show that the IDH1-R132H mutation in gliomas is correlated with a better prognosis compared to wild-type gliomas. This difference was mainly mediated through CX3CL1/CX3CR1 chemotaxis, which recruits NK cells.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…37 In gastric adenocarcinoma, tumor cells secreting CX3CL1 can recruit T cells and NK cells, thus, activating both the adaptive and innate immune responses, leading to prolonged survival. 38 Herein, we show that the IDH1-R132H mutation in gliomas is correlated with a better prognosis compared to wild-type gliomas. This difference was mainly mediated through CX3CL1/CX3CR1 chemotaxis, which recruits NK cells.…”
Section: Introductionmentioning
confidence: 96%
“…demonstrated that CX3CL1/CX3CR1 can reduce the invasion of glioma cells . In gastric adenocarcinoma, tumor cells secreting CX3CL1 can recruit T cells and NK cells, thus, activating both the adaptive and innate immune responses, leading to prolonged survival …”
Section: Introductionmentioning
confidence: 99%
“…Endothelium holds a crucial role regarding the expansion of inflammation, through expression of adhesion molecules such as selectins [55], the intracellular adhesion molecule-1 (ICAM-1) [56], and CX3CL1 (fractalkine) [57] that regulate inflammatory cell recruitment. The effect on vascular wall, along with the partly specified changes on glycocalyx [58], is increased permeability that in AKI, is expressed as proteinuria [58, 59].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence has indicated that CX3CL1 plays an important role in regulating cell invasion, proliferation and migration of inflammatory cells and various cancer cell lines (51). For example, the expression of CX3CL1 is associated with the metastatic rate and a poor prognosis of patients with prostate cancer (19).…”
Section: Discussionmentioning
confidence: 99%